2017
DOI: 10.18332/tpc/69392
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use: comparing smokers, vapers, and dual users on characteristics and motivational factors

Abstract: INTRODUCTION This study examined vaping behaviour, precursors of vaping, and motivational differences between smokers, dual users and vapers. The objectives were to assess a) vaping characteristics and reasons for use, b) differences in motivational factors and behavioural precursors associated with e-cigarette use, and c) socio-demographic and motivational factors associated with electronic cigarette use. METHODS A cross-sectional survey among 259 vapers, 135 smokers, and 83 dual users was conducted in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 49 publications
3
22
0
1
Order By: Relevance
“…In the general NHIS, we included adults who self‐identified as non‐Hispanic White, non‐Hispanic Black or African–American, non‐Hispanic Asian (hereafter referred to as NHPI, Whites, Blacks, and Asians), and Hispanic, and excluded those with multiple race/no primary race selected to avoid non‐identification of NHPI. In both surveys, we excluded participants who were both current E‐cigarette users and conventional cigarette smokers, as their characteristics may differ from those of E‐cigarette users only (Schoren, Hummel, & de Vries, ). In both surveys, participants who responded “refused,” “don't know,” and “not ascertained” were coded as missing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general NHIS, we included adults who self‐identified as non‐Hispanic White, non‐Hispanic Black or African–American, non‐Hispanic Asian (hereafter referred to as NHPI, Whites, Blacks, and Asians), and Hispanic, and excluded those with multiple race/no primary race selected to avoid non‐identification of NHPI. In both surveys, we excluded participants who were both current E‐cigarette users and conventional cigarette smokers, as their characteristics may differ from those of E‐cigarette users only (Schoren, Hummel, & de Vries, ). In both surveys, participants who responded “refused,” “don't know,” and “not ascertained” were coded as missing.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these limitations, this study provides several new contributions to research. In this study, dual users (E‐cigarettes and cigarettes) were removed from consideration because studies have shown that this group has characteristics that differ from those of E‐cigarette users, and because E‐cigarettes are sometimes used as a cessation tool among current smokers (Schoren et al, ). Consequently, we were not able to establish differences between dual users and E‐cigarette users across race/ethnicity.…”
Section: Limitationsmentioning
confidence: 99%
“…Research has presented several differences between exclusive e-cigarette users and dual users, but the variability in results and definitions used makes it difficult to compare these differences [19]. Review of relevant literature has identified four clusters of differences between dual users and e-cigarette users [9,13,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. While previous research looked at differences between dual users and exclusive e-cigarette users on an individual factor level or combined two clusters in an analysis, the goal of our study is to provide aggregated data by combining all the clusters of factors identified with machine learning [9,13,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception differed between dual users and exclusive e-cigarette users [19]. More often, partners, family, friends, and colleagues of e-cigarette users were fellow e-cigarette users [24,30]. E-cigarette users also had less desire for cigarette smoking than dual users, and they found it easier than dual users not to smoke [23,24,30].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with smokers who switch to vaping completely, dual users were reported to have lower education and income4 and to be more likely to have smoking peers 5. They recourse to cigarettes in stressful situations and when rapid nicotine uptake is required,6 7 but also in hedonic situations 8.…”
Section: Introductionmentioning
confidence: 99%